25. LIMB SALVAGE SURGERY FOR PROXIMAL HUMERAL OSTEOSARCOMA BY CLAVICULA PRO HUMERO RECONSTRUCTION: A CASE REPORT (Vietnam Journal of Community Medicine, 2025)
Background: The proximal humerus is a common site of osteosarcoma in children. The selection of limb salvage technique is difficult and based on the invasion of sarcoma in the proximal epiphysis of the humerus and in the soft tissue. Due to the rotator cuff and the deltoid muscle are sacrified, the functions of shoulder will be restricted after reconstruction. There are various reconstruction procedures for limb salvage such as prostheses, arthrodesis, sling procedure using free vascularized fibular graft... but these are difficult, sophisticated surgery with many complications reported. Objective: In this report, we describe a patient with an osteosarcoma of the proximal humerus in which limb salvage surgery is performed by clavicula pro humero reconstruction after large resection of the tumor. To our knowledge, the use of this procedure in such a case has not been previously described in Vietnam.Summary of medical history: A 17-year-old male patient was diagnosed with osteosarcoma of the upper head of the left humerus. After 3 chemotherapy sessions, the tumor shrank in size and had a clearer boundary, however, the head of the bone had been invaded. On March 9, 2024, the patient underwent a wide surgical excision of the cancerous mass including the entire head and the upper third of the left humerus. The left clavicle was completely removed, leaving the acromioclavicular joint, then rotated and grafted onto the remaining left humerus and firmly fixed with a locking screw plate.The microscopic findings shows only osteosclerosis without any malignant and inflammatory cells indicating a well sensible chemotherapy. The surgical wound heals well. There are good callus formation at the junction of humerus-clavicle graft after 6 months of surgery. The patient feels satisfaction with no pain anf good perception. At the time of 15 months post-op, the bone graft heals well. The patient can carry a 7 kg-object. He can move the left shoulder with 60o in flexion and 50o in extension, 55o in abduction. The functions of the left elbow, wrist and hand are normal. The MSTS is 24/30 points. There are no local recurrence and distant metastasis noticed. Conclusion: Limb salvage surgery for proximal humeral osteosarcoma by clavicular pro humero reconstruction may be a useful procedure. This is a simpler and easier surgical technique in comparison with other methods. Even the functions of shouder are restricted but the patient feels satisfy with his arm saved with normal functions of the elbow, wrist and hand.
Keywords: Limb salvage surgery; proximal humeral osteosarcoma; clavicula pro humero reconstruction.